Reducing risks of transactions on marijuana markets - institution of friendship - Běláčková, Vendula, 1982- (2013)
BACKGROUND: Economists depict illicit markets as violent, due to the lack of centralized property rights enforcement. At the same time, the importance of friendship networks and drug sharing is a recently documented feature of the marijuana market. Recent studies show an increased role of acquiring marijuana through friends, especially in settings where drug policy is rather punitive. This thesis extends this research into the norms that marijuana users attribute to their definition friendship. To do this, the thesis conceptualizes friendship as a type of institution that reduces the transaction costs on the market, and like that, it limits the decision making of marijuana market players. DATA: Marijuana market patterns in the Czech Republic and North-Central Florida were analyzed via both qualitative and quantitative research methods. For the purpose of the qualitative study, 44 (resp 66) study participants were marijuana users and retailers recruited at North-Central Florida (resp in the Czech Republic), with the use of respondent-driven sampling. Inclusion criteria into the study was the use of marijuana in the last 12 months. Semi-structured interviews, that took 80 minutes on average, followed an interview guide focused on marijuana use, sharing, purchases, sales and growing, with extensive probes on activities of respondents` "friends", as they defined them. As for the quantitative data, marijuana market modules from two representative general population surveys on substance use were used (CS 2008, NSDUH). METHODS: Qualitative data were analysed with the use of inductive analysis, and were framed into institutional economics theory. Quantitative data were analyzed with the use ordinary logit models. FINDINGS: The study has shown remarkable impact of drug policies on cannabis markets via comparison between the Czech Republic and the U. S. (North-Central Florida).